Exploring Disparities in Influenza Immunization for Older Women. Issue 6 (16th April 2019) - MacCarthy, Sarah; Burkhart, Q; Haviland, Amelia M.; Dembosky, Jacob W.; Wilson‐Frederick, Shondelle; Saliba, Debra; Gaillot, Sarah; Elliott, Marc N.
Abstract : OBJECTIVES: While women obtain most recommended preventive health interventions more often than men, evidence is mixed regarding influenza vaccination for older adults. Therefore, we evaluated sex differences in influenza vaccination among older adults. DESIGN: Nationally representative cross‐sectional survey. SETTING: United States. PARTICIPANTS: A total of 1 252 705 adults, aged 65 years and older, responding to 2013 to 2017 Medicare Consumer Assessment of Healthcare Providers and Systems surveys. MEASUREMENTS: The dependent variable was Healthcare Effectiveness Data and Information Set self‐reported influenza immunization. The primary predictor was sex. Covariates included general health status, education, race/ethnicity, and Medicare Advantage (MA; managed care) vs Fee‐for‐Service (FFS) coverage. RESULTS: After adjusting for health status and other sociodemographic factors, women's immunization was 2% lower than men's immunization in MA, with no significant overall sex difference in FFS. Women were immunized less often than men in 95% of MA health plans, with the largest gaps in low‐immunizing plans. Further analyses revealed variation in sex differences by health status, education, and race/ethnicity in both MA and FFS. Notably in MA, women in poor health were immunized less often than men in similar health (−4%; P < .001). Black women were immunized much less often than black men in both MA and FFS (−5%; P < .001 for each). Hispanic women were immunized less often than Hispanic men in MA (−4%; P < .001) but not within FFS. CONCLUSION: Women in MA experience small disparities overall in influenza immunization, with larger disparities for black and Hispanic women. Providers and MA plans should increase efforts to recommend and monitor immunization for older women, especially black and Hispanic women and those in poor health. Given the potential to reduce morbidity and mortality, equitable access to a critical preventive health service, such as influenza immunization, is crucial for all older adults.